Palliative care and COVID-19: acknowledging past mistakes to forge a better future - Andrade, Camila Rabelo Monteiro de; Luz, Fernanda Silva Trindade; Oliveira, Neimy Ramos de; Kopittke, Luciane; Santa Rosa, Luiza Marinho Motta; Gomes, Angelica Gomides dos Reis; Bartolazzi, Frederico; Francisco, Saionara Cristina; Costa, Felicio Roberto da; Jorge, Alzira de Oliveira; Cimini, Christiane Corrêa Rodrigues; Carneiro, Marcelo; et al. (Frontiers, 2024)
Context: COVID-19 induces complex distress across physical, psychological, and social realms and palliative care (PC) has the potential to mitigate this suffering significantly. Objectives: To describe the clinical characteristics and outcomes of COVID-19 patients with an indication of PC, compared to patients who had no indication, in different pandemic waves. Methods: This retrospective multicenter observational cohort included patients from 40 hospitals, admitted from March 2020 to August 2022. Patients who had an indication of palliative care (PC) described in their medical records were included in the palliative care group (PCG), while those who had no such indication in their medical records were allocated to the non-palliative care group (NPCG). Results: Out of 21,158 patients, only 6.7% had indication for PC registered in their medical records. The PCG was older, had a higher frequency of comorbidities, exhibited higher frailty, and had a higher prevalence of clinical complications and mortality (81.4% vs. 17.7%, p < 0.001), when compared to the NPCG. Regarding artificial life support, the PCG had a higher frequency of dialysis (20.4% vs. 10.1%, p < 0.001), invasive mechanical ventilation (48.2% vs. 26.0%, p < 0.001) and admission to the intensive care unit (53.6% vs. 35.4%, p < 0.001). These differences were consistent across all three waves. Conclusion: A low proportion of patients received PC. Patients in PCG were more fragile, had more clinical complications, and had a higher mortality. On the contrary to our expectations, they received more artificial life support in all three waves. Taken together, these findings suggest that decisions regarding PC indication were made too late, within a context of end-of-life and therapeutic failure.
Keywords: clinical characteristics; COVID-19; frailty; hospitalization; outcomes assessment; palliative care